Essays on Native Modernism Complexity and Contradiction in American Indian Art (National Museum of the American Indian, 2006)
Essays on Native Modernism: Complexity and Contradiction in American Indian Art, which grew out of a symposium held by NMAI in May 2005, explores the legacies of George Morrison (Grand Portage Band of Chippewa, 1919-2000) and Allan Houser (Warm Springs Chiricahua Apache, 1914-1994)-two giants of 20th-century art-as well as investigates the basis of a Native modernism by eliciting a broad discussion about the critical perspectives and practices of Native artists across North America. Also examined is the place of Native modernism in the canon of American art and the currents of influence between them.